2003
DOI: 10.1038/sj.bjc.6600813
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of polymorphonuclear leukocyte elastase in breast cancer tissue is associated with tamoxifen failure in patients with advanced disease

Abstract: Besides a variety of other proteases, polymorphonuclear leukocyte elastase (PMN-E) is also suggested to play a role in the processes of tumour cell invasion and metastasis. Yet, there is only limited data available on the relation between the tumour level of PMN-E and prognosis in patients with primary breast cancer, and no published information exists on its relation with the efficacy of response to systemic therapy in patients with advanced breast cancer. In the present study, we have measured with enzyme-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 50 publications
1
35
0
Order By: Relevance
“…No association with outcome was found for PR3 neither, which might be partially explained by its very low production by tumor cells. As another study by Foekens et al 9 reported the association between high NE levels and tamoxifen failure in advanced breast cancer patients, we investigated the predictive value of NE in our subgroup of ER-positive tamoxifen-only treated patients, but did not find any association with clinical outcome. However, direct comparisons could not be made due to differences in assays and patient cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No association with outcome was found for PR3 neither, which might be partially explained by its very low production by tumor cells. As another study by Foekens et al 9 reported the association between high NE levels and tamoxifen failure in advanced breast cancer patients, we investigated the predictive value of NE in our subgroup of ER-positive tamoxifen-only treated patients, but did not find any association with clinical outcome. However, direct comparisons could not be made due to differences in assays and patient cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…The histological grade, as well as the ER status was significantly associated with clinical outcome in univariate analysis. All these variables were further compared in a multivariate model with backward stepwise selection based on hypotheses tests using likelihood ratios, starting only with the variables that had a As several studies reported CCNE and NE as markers predicting endocrine therapy failure, 5,9 we conducted a subgroup analysis in the 110 ER-positive tumors from patients treated with adjuvant tamoxifen only. The results regarding NE, PR3, CCNE1 and CCNE2 were visualized as Kaplan-Meier curves in Figure 2.…”
Section: Ne Pr3 Ccne1 and Ccne2 Expression Levels And Patient Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, a model including all established clinicopathological factors, irrespective of statistical significance in univariate analysis as has been recommended by Altman and Lyman (1998) for exploratory studies into new prognostic factors, was fitted with backward stepwise selection of significant factors based on their likelihood ratio. In a second block, the contributions of cyclin-E (as a continuous, log-transformed variable), treatment (radiotherapy, endocrine therapy or chemotherapy) and their interactions (by inclusion of product variables as described (Altman and Lyman, 1998;Harbeck et al, 2002;Foekens et al, 2003)) were investigated with the same selection procedure. Survival curves were generated using the method of Kaplan and Meier (1958).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Of the 3 general classes of human elastase that have been characterized [polymorphonuclear neutrophil elastase or leukocyte elastase, metalloelastase (or MMP12), and pancreatic elastase], the neutrophil elastase is highly expressed in human breast cancers and has been implicated in the processes of tumorigenesis (32). Importantly, the level and enzymatic activity of neutrophil elastase are an independent prognostic marker for breast cancer survival and clinical outcome as well as for metastasis progression of various cancers (33)(34)(35)(36). In this report, we demonstrate that the dietary phytochemical I3C is a noncompetitive inhibitor of human elastase enzymatic activity that directly accounts for the disrupted cyclin E processing in human breast cancer cells, and therefore we have identified the first functional cellular target protein for I3C that mediates the indole-induced G 1 cell-cycle arrest of human cancer cells.…”
mentioning
confidence: 99%